Social Marketing and Social Responsibility. A theoretical confrontation - Vargas Merino, Jorge Alberto (2020)
Social Marketing and Social Responsibility. A theoretical confrontation Abstract Social marketing and social responsibility are terms that are currently relevant and related to addressing a critical and complex social reality. In the contemporary academic and scientific world they are often considered as similar concepts despite the conceptual and structural difference between them. This academic article deals with a systematic review of scientific literature where 124 articles from different disciplines were consulted in diverse databases; 57 of them were considered relevant from their inclusion in indexed or arbitrated journals, besides reflecting relevant and concise information generated in the last 5 years. However, articles out of the 5-year range were also considered to evaluate and analyze the evaluation of concepts on social marketing. The analysis of these sources allowed an approximation to the theoretical evolution of this aspect to conclude that although social marketing and social responsibility are related concepts they should not be confused. Especially, because the first is considered a tactic that takes place in a certain period of time, it focuses on a target audience to influence a desired behavior or idea, while the second is considered a strategy assumed by a company in all its aspects aimed at stakeholders in a longer term. Key words: Social marketing, social responsibility, theory, stakeholders, target audience.